IDENTIFICATION OF AEDES AEGYPTI BREEDING SITES IN URBAN SPACES OF SANTO TOMÉ (SANTA FE) DURING 2023–2024 EPIDEMIC SEASON: A PUBLIC HEALTH VOLUNTEERING EXPERIENCE (SigMe, 2025)
Dengue is a globally expanding disease transmitted by the Aedes aegypti mosquito. Certain commercial and social activities can promote the formation of breeding sites for the vector in urban areas, thereby increasing the risk of transmission during epidemic periods. This study aimed to analyze the condition of various spaces, such as garden centers, tire shops, and cemeteries, in relation to the development of breeding sites in the city of Santo Tomé. During the 2023-2024 epidemic season, 12 surveys were conducted, in which 67 sites were surveyed; 14 of them confirmed the presence of the mosquito. The conditions of the garden centers and tire shops are relatively moderate, whereas the municipal cemetery and public pet drinking fountains require specific interventions to reduce breeding sites. Collaboration among university volunteers, municipal staff and city residents contributed to strengthening local public health.
Keywords: Mosquito; Dengue; Breeding sites; Citizen participation; Prevention